Economic development - Todaro, Michael P.; Smith, Stephen C. 1955- (Pearson, 2020)
Economic development, 13th edition by Todaro and Smith is the leading textbook in the field of development economics. It provides student with a complete and balanced introduction to the requisite theory driving policy issues and the latest research. Todaro and Smith take a policy-oriented approach, presenting economic theory in the context of critical policy debates and country-specific case studies to show how theory relates to the problems and prospects of developing countries.